2018
DOI: 10.5152/cjms.2018.301
|View full text |Cite
|
Sign up to set email alerts
|

Case Report of Systemic Tularemia in Cyprus

Abstract: Tularemia is a zoonotic infectious disease in the Northern Hemisphere, which is caused by gram-negative Francisella tularensis bacteria with four subtypes. In this article, a case of a 5-year-old girl with oculoglandular, oropharyngeal, and typhoid tularemia accompanied by lymph nodes in the abdomen has been presented. Amoxicillin-clavulanic acid treatment was first applied to the patient who had high fever, neck lymphadenopathy, and crypts in the tonsils.Intramuscular ceftriaxone therapy was started after the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Moreover, there is one case (a 5-year-old girl) of tularemia reported in the http://jad.tums.ac.ir Published Online: March 31, 2024 literature so far, and it has been reported that this case was in contact with an infected wild rabbit. In the patient's anamnesis, there was a history of contact with wild rabbits hunted by his father who was a hunter (8). Our study is the first to carry out research that showed tularemia seroprevalence in our country among hunters who are considered to be risk groups and showed a high seroprevalence (17%).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Moreover, there is one case (a 5-year-old girl) of tularemia reported in the http://jad.tums.ac.ir Published Online: March 31, 2024 literature so far, and it has been reported that this case was in contact with an infected wild rabbit. In the patient's anamnesis, there was a history of contact with wild rabbits hunted by his father who was a hunter (8). Our study is the first to carry out research that showed tularemia seroprevalence in our country among hunters who are considered to be risk groups and showed a high seroprevalence (17%).…”
Section: Discussionmentioning
confidence: 73%
“…Tularemia is an infection that can be seen all over the world, although its prevalence is higher, especially in the northern hemisphere (between 30-71° latitudes) (3)(4)(5). Tularemia cases have recently been reported in Europe (6), Turkey (7), Iran (4), Jordan (1) and also Cyprus (8). The dis-48 http://jad.tums.ac.ir Published Online: March 31, 2024 ease is referred to by different names in various geographical regions such as Francis' Disease, Pahvant Valley plaque, hunters' disease, rabbit fever, deer fly fever, and tick fever (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Little is known about tularemia in Northern Cyprus. A single case was reported in 2017 by Uncu et al [9] .…”
Section: Dear Editormentioning
confidence: 95%